An Assessment of Information Control: Understanding Library Service Quality from Users’ Perspectives - Sayekti, Retno; Aditya, Muhammad; Simahate, Tessa; Devianty, Rina (Evidence Based Library and Information Practice, 2022)
Objective – This study aims to measure library users’ perceptions of the quality of information control using LibQual, a survey instrument that measures library users’ minimum perceived and desired levels of service quality across three dimensions: Effect of Service, Library as Place, and Information Control. Numerous studies using LibQual have emphasized the service aspect, while quality of information control has received less attention. Previous studies have reported low quality of information control in academic libraries.Methods – A descriptive survey was conducted at the library of the Universitas Islam Negeri Sumatera Utara (UINSU), Medan, Indonesia, where active members of the library total 49,892. Using proportional random sampling, 100 completed surveys were obtained from a total population of 49,892.Results – This study shows that the quality of information control in the library of UINSU Medan does not meet minimum user expectations. Nevertheless, ease of navigation of information was perceived as acceptable. The study also reveals that the library has promoted information services through exhibition activities, user education activities, and social media.Conclusion – The findings suggest the need for libraries to improve the quality of information services, including content of information, access protocols, search time, ease of navigation, interface, and access from outside the campus. Further, libraries need to conduct continuous service quality evaluation on a regular basis (using tools such as LibQual) to understand the needs of users in terms of information control better. The results from the present study provide strong evidence to support a recommendation that, in general, universities should provide required resources and funding for libraries to improve information services to ensure that the libraries meet quality standards.